2019
DOI: 10.5397/cise.2019.22.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Delaminated Rotator Cuff Tear: Concurrent Concept and Treatment

Abstract: Delaminated rotator cuff tear pertains to the horizontal split of the tendon substance. As reported previously, the presence of a delaminated tear and incidence of delaminated rotator cuff tear ranges from 38% to 92%. The different strain intensities applied across the rotator cuff tendon, and the shear stress between the bursal and articular layers seem to play a role in its pathogenesis. In a delaminated rotator cuff tear, the degree and direction of retraction between two layers differ, with accompanying in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…These tears can occur in the bursal surface, the articular surface, or the tendon intrasubstance [ 7 , 8 ]. The latter is called a “delaminated tear” and is described as a horizontal split of the tendon substance [ 9 , 10 ]. A delaminated tear is located between the articular and bursal layers of the tendon, with or without articular or bursal side tears [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tears can occur in the bursal surface, the articular surface, or the tendon intrasubstance [ 7 , 8 ]. The latter is called a “delaminated tear” and is described as a horizontal split of the tendon substance [ 9 , 10 ]. A delaminated tear is located between the articular and bursal layers of the tendon, with or without articular or bursal side tears [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some delaminated tears, intratendinous fibers separated by horizontal splitting are retracted to varying degrees [ 7 , 12 , 13 ]. Identifying the delaminated tear in preoperative MRI is important because arthroscopic detection is difficult when there are no accompanying articular or bursal side tears [ 8 , 10 ]. Thus, it is imperative to determine the precise location and size of the delaminated tears of the rotator cuff preoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…21 En masse repair is performed by passing a suture through the bursal and articular layers simultaneously. 19 Although en masse repair shows favorable results, 10,11,19 individual repair of each layer, known as layer-by-layer repair, has been recommended for anatomic restoration. 7,25 The goal of layered repair is to prevent tension and length mismatch between the layers.…”
mentioning
confidence: 99%
“…The reported incidence of delaminated RCTs is between 32% and 88%. 10 Boileau et al 2 reported delaminated tears in 32% of patients after arthroscopic repair of medium or large chronic full–thickness RCTs. Han et al 6 reported an incidence of 88%.…”
mentioning
confidence: 99%
“…Although the term delamination is commonly used, it has not been clearly defined. 15 Various definitions are used, and there is no standard classification depending on radiologic images or arthroscopic findings. 6,17 Recently, the "everted type," bursal-sided, partial-thickness tear was reported as being associated with worse pain and range of motion (ROM) preoperatively than a simple bursal-sided tear.…”
mentioning
confidence: 99%